Evaluation of Color Contrast Sensitivity in Dyslexic Children - Alireza Mohamadi; Ebrahim Jafarzadehpur (Vesnu Publications, 2014)
Introduction: Although there is a consensus about the importance of vision perception in reading, its role in development of dyslexia is highly debated. In order to understand the relationship between dyslexia and disorders of visual perception, we have compared color opponent contrast sensitivity in dyslexic children with that in normal subjects. Materials and Methods: 3 dyslexic and 3 normal children participated in this study. Their responses to stimuli produced by means of "Pattern Generator" software were recorded in three spatial frequencies: 5, 8, and 18 cycles per degree (cpd). In each spatial frequency, contrast sensitivity test was executed in two different levels (pattern detection and color discrimination) once in yellow background and once again in blue background. Results: In general, there was no significant difference between dyslexic and normal children in almost all the tests performed. Nevertheless, dyslexic subjects have shown reduced sensitivity in pattern detection both in yellow and blue backgrounds, yet they had better sensitivity than normal subjects in color discrimination. Conclusion: The results from comparison between dyslexic and control groups showed that color contrast sensitivity cannot be a proper differential indicator for dyslexia. It suggests that dyslexia does not affect all functions of the visual system. However, in dyslexia we may have anomalous perceptual responses even with normal basic and primary visual functions. Keywords: Dyslexia, Vision, Contrast Sensitivity, Color Opponent